Effects of antipsychotics on bone mineral density and prolactin levels in patients with schizophrenia: a 12‐month prospective study. (22nd January 2014) - Wang, Mengxin; Hou, Ruihua; Jian, Jia; Mi, Guolin; Qiu, Huimin; Cao, Bingyu; Tang, Maoqin
<x xml:space="preserve">Abstract</x> Objective Effects of conventional and atypical antipsychotics on bone mineral density (BMD) and serum prolactin levels (PRL) were examined in patients with schizophrenia. Methods One hundred and sixty‐three first‐episode inpatients with schizophrenia were recruited, to whom one of three conventional antipsychotics (perphenazine, sulpiride, and chlorpromazine) or one of three atypical antipsychotics (clozapine, quetiapine, and aripiprazole) was prescribed for 12 months as appropriate. BMD and PRL were tested before and after treatment. Same measures were conducted in 90 matched healthy controls. Results Baseline BMD of postero‐anterior L1–L4 range from 1.04 ± 0.17 to 1.42 ± 1.23, and there was no significant difference between the patients group and healthy control group. However, post‐treatment BMD values in patients (ranging from 1.02 ± 0.15 to 1.23 ± 0.10) were significantly lower than that in healthy controls (ranging from 1.15 ± 0.12 to 1.42 ± 1.36). The BMD values after conventional antipsychotics were significantly lower than that after atypical antipsychotics. The PRL level after conventional antipsychotics (53.05 ± 30.25 ng/ml) was significantly higher than that after atypical antipsychotics (32.81 ± 17.42 ng/ml). Conditioned relevance analysis revealed significant negative correlations between the PRL level and the BMD values after conventional antipsychotics. Conclusion The increase of PRL might be an important risk factor leading to a high prevalence of osteoporosis in patients with schizophrenia on long‐term conventional antipsychotic medication. Copyright © 2014 John Wiley & Sons, Ltd.